APLIKASI PELAPORAN KERJA CLEANING SERVICE DENGAN METODE WATERFALL - Lee, Francka Sakti; Nurprihatin, Filscha; Honni, Honni; Santoso, Andi Putra; Tampinongkol, Felliks F (Infotech: Journal of Technology Information, 2024)
After the Covid-19 pandemic passed, digital transformation occurred, namely the use of technology in various activities of human life, including at work. Regardless of age, position, or educational background, we all have to learn so as not to be left behind. Cleaning service (CS) work has been seen as easy and does not require technology, except for WhatsApp Messenger or Group communication tools. The ship engine distributor company has office and warehouse areas that require CS services to maintain cleanliness. So far, coordination of work or the presence of CS personnel has been carried out through face-to-face briefings and WhatsApp. However, after restrictions on meeting (physical distancing), PSBB, etc., it seems that the use of WhatsApp is considered insufficient to accommodate work needs in the field for CS. This research aims to design a Cleaning service application to handle difficulties in the field for managing work and reports. The system development method used is the Waterfall Model method. The results of this research aim to provide convenience for CS coordinators and companies in managing CS performance, making reports, and improving the quality of cleaning services in the field.ABSTRAKSetelah masa pandemi Covid-19 berlalu, terjadi transformasi digital yaitu penggunaan teknologi pada berbagai aktivitas kehidupan manusia, termasuk dalam bekerja. Tidak memandang usia, jabatan, atau latar belakang pendidikan, kita semua harus belajar agar tidak tertinggal. Pekerjaan cleaning service (CS) selama ini dipandang mudah dan tidak memerlukan teknologi, kecuali alat komunikasi WhatsApp Messenger atau Group. Perusahaan distributor mesin kapal memiliki area kantor dan gudang yang memerlukan jasa CS untuk menjaga kebersihan. Selama ini koordinasi pekerjaan atau kehadiran personil CS dilakukan melalui briefing tatap muka dan WhatsApp. Namun setelah terjadi pembatasan untuk bertemu (physical distancing), PSBB, dll, tampaknya penggunaan WhatsApp dinilai kurang untuk mengakomodir kebutuhan pekerjaan di lapangan untuk CS. Penelitian ini bertujuan merancang aplikasi Cleaning service untuk menangani kesulitan di lapangan untuk pengaturan dan pelaporan pekerjaan. Metode pengembangan sistem yang digunakan adalah metode Model Waterfall. Hasil penelitian ini bertujuan memberikan kemudahan bagi koordinator CS dan perusahaan dalam mengatur kinerja CS, membuat pelaporan, dan meningkatkan kualitas pelayanan kebersihan di lapangan.